ANALISIS KEDWIBAHASAAN TUTURAN TIKTOKERS SEBAGAI ALTERNATIF MEDIA PEMBELAJARAN BAHASA INDONESIA KELAS IX - Aprilia Ekawati Rosliana; Any Budiarti; Marlia (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Every content creator certainly has their own characteristics, one of which is seen from their attitude when speaking. A bilingual or bilingual content creator will add to his image in the eyes of his followers. Therefore, research was conducted on the analysis of Tiktokers' speech as an alternative to class IX Indonesian learning media. The purpose of this study is to describe the forms of language in Tiktokers speech in response content on TikTok, as well as describe the relevance of the results of bilingual analysis of Tiktokers speech as a Indonesian learning medium in class IX. The method used in this study is using qualitative methods with a descriptive approach. The data analyzed is in the form of bilingual Tiktokes speech sourced from the TikTok application with stitch content categories (responses). The source of data in this study is content creators (Tiktokers). Data collection in this study was carried out by opening the TikTok application, listening to TikTok videos with stitch content categories, selecting video samples, downloading selected TikTok videos, and transcribing Tiktokers' speech. The form of realization of Tiktokers bilingualism is the ability subordinative bilinguals of 3 speeches, multiple bilinguals obtaining 1 ultterances and coordinating bilingual ability of 2 utterances. The results of the bilingual analysis of Tiktokers speech on stitch content (responses) proved to be relevant to learning media, especially interactive media in the form of audio visuals. In other word, TikTok can be used as response text learning medium in class IX.